2018
DOI: 10.1021/acs.energyfuels.8b03688
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Acid Gas Sorption Properties of Oxidatively Degraded Supported Amine Sorbents

Abstract: Word 2010, single-column, double-spaced (2013) This template is a guide to be used to prepare manuscripts for submission. Please consult the Instructions to Authors or a recent issue of the journal for detailed guidelines and procedures for submission. This template is intended to benefit to the author in that the entire manuscript (text, tables, and graphics) may be submitted in one file. Inserting graphics and tables close to the point at which they are discussed in the text of the manuscript can also be a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The sample was initially heated at 110 °C for 2 h under He and then equilibrated at 35 °C for 1 h. Cycles of adsorption for 3 h at 35 °C and desorption for 2 h at 110 °C were then performed. He is used as a balance gas in the CO 2 adsorption measurements by TGA, because it is a nonadsorbing gas compared to CO 2 when using amines for CO 2 capture, and the use of a CO 2 /He mixture in the current study allows for comparison with similar amine-loaded materials reported in the literature. ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was initially heated at 110 °C for 2 h under He and then equilibrated at 35 °C for 1 h. Cycles of adsorption for 3 h at 35 °C and desorption for 2 h at 110 °C were then performed. He is used as a balance gas in the CO 2 adsorption measurements by TGA, because it is a nonadsorbing gas compared to CO 2 when using amines for CO 2 capture, and the use of a CO 2 /He mixture in the current study allows for comparison with similar amine-loaded materials reported in the literature. ,, …”
Section: Methodsmentioning
confidence: 99%
“…He is used as a balance gas in the CO 2 adsorption measurements by TGA, because it is a nonadsorbing gas compared to CO 2 when using amines for CO 2 capture, and the use of a CO 2 /He mixture in the current study allows for comparison with similar amine-loaded materials reported in the literature. 7,27,28 Column breakthrough experiments were performed on a custombuilt apparatus described elsewhere. 29 In brief, for a typical experiment, a module containing PEI-CA-SiO 2 monolithic fibers was wrapped in heat tape and dried at 90 °C for 30 min under a 20 sccm flow of dry N 2 and was then brought to the desired adsorption temperature.…”
Section: ■ Experimentsmentioning
confidence: 99%
“…49−51 Typically, the oxidation of the amine polymers 52 produces less basic imine, amide, and other species, which are less effective CO 2 sorbents. Amine oxidation in solid sorbents has been widely studied by Sayari, 53−56 Jones, 57,58 and others, 51,59,60 with oxidation mitigation strategies including design of more oxidation-resistant sorbents 30,31,58,61,62 as well as adding stabilizers to the amine formulations. 46,59 For example, Min et al have used 1,2-epoxybutane and found that the PEI/SiO 2 composite retained about 92% of its working capacity after exposure in an O 2containing simulated flue gas (15% CO 2 ) mixture for 30 days at 110 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, physical aging and oxidation are two factors that can drastically impact the physical properties and functionality of any polymeric materials. Typically, the oxidation of the amine polymers produces less basic imine, amide, and other species, which are less effective CO 2 sorbents. Amine oxidation in solid sorbents has been widely studied by Sayari, Jones, , and others, ,, with oxidation mitigation strategies including design of more oxidation-resistant sorbents ,,,, as well as adding stabilizers to the amine formulations. , For example, Min et al have used 1,2-epoxybutane and found that the PEI/SiO 2 composite retained about 92% of its working capacity after exposure in an O 2 -containing simulated flue gas (15% CO 2 ) mixture for 30 days at 110 °C . Srikanth and Chuang studied TEPA/SBA-15 composites and found that addition of poly­(ethylene glycol) (200 or 600 Da) improved the adsorption performance of the sorbents and the oxidative degradation resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stability is a dominant factor that determines the lifetime of amine-functionalized adsorbents. The oxidative degradation of amine-loaded adsorbents principally results in the chemical instability of loaded amines, 105 producing new characteristic bonds including carbonyl (CQO), 134,254,[382][383][384][385] aliphatic CQC, 382 heterocyclic CQN, 134,[382][383][384] and aromatic CQC 382 owing to the formation of acid, amide, imide, and/or urea linkages. 134,254,[382][383][384][385][386] 13 C cross-polarization magic-angle spinning (CP-MAS) solid state NMR, 254,[381][382][383][384][385][386] XPS, 382 diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, 254,381,[383][384][385]387,388 and FT-Raman spectroscopy 254 are usually employed to examine the effect of oxidative treatments on solid adsorbents.…”
Section: Pathway Of Oxidative Degradationmentioning
confidence: 99%